Association between hospital internal medicine physician workforce and patient admissions during the COVID-19 pandemic in Japan - Seiji Hamada; Takuhiro Moromizato; Masashi Narita; Kiyosu Taniguchi; Kenji Shibuya; Yasuharu Tokuda (BMC Health Services Research, 2023)
Abstract Background Hospital physician workforce in Japan is the lowest among developed countries. Many patients with novel coronavirus disease 2019 (COVID-19) with high risk of mortality could not be hospitalized during case surges in Japan and only about 5% of total acute care beds were used as COVID-19 beds nationwide. However, the relationship between the number of hospital physicians and patient admissions remains unclear. Thus, we aimed to evaluate this relationship in areas with the highest incidences during the surges. Methods Data collection was performed for teaching hospitals accredited with the specialty of internal medicine in three prefectures which experienced the highest COVID-19 incidences in Japan (Tokyo, Osaka, Okinawa). Association was examined between the number of full-time physicians (internal medicine staff physicians and residents) and admissions of internal medicine patients through ambulance transport from April 2020 to March 2021. Analysis was conducted separately for community hospitals and university hospitals because the latter have roles as research institutions in Japan. Community hospitals included private, public, and semi-public hospitals. Results Of 117 teaching hospitals in three prefectures, data from 108 teaching hospitals (83 community hospitals and 25 university hospitals) were available. A total of 102,400 internal medicine patients were admitted to these hospitals during the one-year period. Private hospitals received the greatest mean number of patient admissions (290 per 100 beds), followed by public hospitals (227) and semi-public hospitals (201), and university hospitals (94). Among community hospitals, a higher number of resident physicians per 100 beds was significantly associated with a greater number of patient admissions per 100 beds with beta coefficient of 11.6 (95% CI, 1.5 to 21.2, p = 0.025) admissions by one physician increase per 100 beds. There was no such association among university hospitals. Conclusions Community hospitals with many resident physicians accepted more internal medicine admissions through ambulance transport during the COVID-19 pandemic. An effective policy to counter physician shortage in hospitals in Japan may be to increase internal medicine resident physicians among community hospitals to save more lives.